Legal Formulation to Overcome Base-Erosion and Profit-Shifting Practices of Digital-Economy Multinational Enterprise in Indonesia - Russel Butarbutar (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2022)
This study discusses Indonesian legal strategies and formulations to handle tax avoidance originating from Base Erosion Profit Shifting (BEPS) carried out by the digital-economy multinational enterprise. It is a normative (doctrinal) study supported by non-doctrinal methods to reveal the truth based on the logic of legal scholarship. It also compared the practices to the tax provisions, legislation, and cases in India, the United Kingdom, Australia, and Malaysia. At least two theories underlie the study. The first is the legal theory of justice, certainty, and expediency from Gustav Radbruch. The second is the theory of international cooperation. The study found several points. First, multinational enterprise strategies avoid tax by means of Permanent Establishment techniques in low-tax jurisdictions, transfer pricing, and tax treaty shopping. Second, to tackle the multinational enterprise that conducts BEPS in the field of the digital economy, (1) all countries have developed and amended laws and regulations related to e-commerce taxation and the digital economy; and (2) all countries carry out international cooperation, both bilaterally and multilaterally through tax treaties, MLI, and CbC reporting. DOI: https://doi.org/10.22304/pjih.v9n3.a2